The Authority of Government and PT Pertamina On the Pricing of 12-Kg LPG - Dina Rachmawati (Hang Tuah Law Journal, 2018)
In 2004, the price of 12-kg LPG in Indonesia fluctuated within a week. According to BPK report between 2011 and 2012, Pertamina lose 77 Trilion rupiahs in LPG sales. As a state-owned company, Pertamina decided to increase the LPG price up to 68% from the current price. The government acts to regulate the LPG price twice in a week resulting in a huge margin for agent and consumer. However, it is clearly interesting to see the boundaries of authority between PT Pertamina and Government in ricing 12-kg LPG for people. The Ministrial Regulation of Energy and Mineral Sesources No.26 year 2009 should be revised as it is against the above regulation or ‘lex posteriori derogat legi inferiori’. The regulation against this regulation includes Act No. 22 year 2001, In accordance to all of the regulations mentioned here, government should regulate things with effect on many people needs in society. This research aims to analyze how is the government’s responsibility on public interest and people live. And basically, the state is responsible to concern on what its people need in order to conduct a competitive economy.